2016
DOI: 10.1111/fme.12180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tagging on migration behaviour, survival and growth of hatchery‐reared Atlantic salmon smolts

Abstract: The effects of four different tagging methods (PIT, anchor T‐tag, Carlin tag and dummy radio transmitter) on survival, behaviour and growth of Atlantic salmon smolts during their downstream migration were examined in semi‐natural circular channels during a natural migration period in spring. Survival of smolts was high and tagging wounds healed well in all tagging groups. Tag loss rates were generally low, being the highest (2.5%) in the dummy radio transmitter group. Total length and body mass of the tagged a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
(141 reference statements)
1
6
0
Order By: Relevance
“…However, tagging effects are thought to be negligible, at this methodology is applied in many studies with none to very limited observed mortality (e.g. Huusko et al, 2016). Additionally, control fish may not have been representative of the treatment fish due to the acquisition process pre-selecting for the least damaged survivors.…”
Section: Discussionmentioning
confidence: 99%
“…However, tagging effects are thought to be negligible, at this methodology is applied in many studies with none to very limited observed mortality (e.g. Huusko et al, 2016). Additionally, control fish may not have been representative of the treatment fish due to the acquisition process pre-selecting for the least damaged survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream movement activity of smolts increases as the river temperature rises, usually close to or above 10°C (Lundqvist et al, 2010; Ruggles, 1980). This increase in swimming activity together with rising temperature was evident also in smolts of hatchery origin released in the river (Karppinen et al, 2014) and was discernible even in fish farm experimental conditions (Huusko et al, 2016; Martin et al, 2012). The hatchery smolts used in this study were well smoltified according to their external appearance and behaviour.…”
Section: Discussionmentioning
confidence: 82%
“…Other PIT‐tagging studies with salmonids have used some, but not all, of these approaches to measure growth, and never simultaneously, to the best of our knowledge. Commonly, mean size through time has been compared between tagged groups and untagged controls, either alone (Huusko et al, 2016; Prentice et al, 1990; Sigourney et al, 2005) or in conjunction with: (a) growth rate from mean size of tagged and untagged fish (Bateman & Gresswell, 2006; Tiffan et al, 2015) or individual growth rate in weight of tagged fish only (Acolas et al, 2007; O'Donnell & Letcher, 2017; Ostrand et al, 2011; Richard et al, 2013). Comparison of individual growth rates of tagged and untagged fish provides a detailed examination of tagging effects (e.g., Larsen et al, 2013), but this approach is comparatively rare given the methodological challenges of identifying individuals in untagged control groups.…”
Section: Discussionmentioning
confidence: 99%